Why does diseased parathyroid appear weak or heterogenous intensity during intraoperative near-infrared autofluorescence? - Huang, Shih-Ming (Frontiers in Endocrinology, 2023)
Background During intraoperative autofluorescence, the imaging intensity of diseased parathyroid glands is often lower than that of normal parathyroid glands, and some diseased glands especially those in secondary hyperparathyroidism (HPT) show heterogeneous intensities. This study aimed to investigate the reasons for these findings. Methods After formalin and paraffin fixation and bivalve cutting, 18 diseased glands from patients with primary HPT, 35 diseased parathyroid glands from patients with uremic HPT, and the surrounding thyroid and thymus tissues were measured using near-infrared autofluorescence with a Fluorobeam imaging system (Fluoptics, France). None of the tissues were stained with indocyanine green. Hematoxylin and eosin staining matched the intensity of the autofluorescence. Results Using the bright white intensity of the adult normal parathyroid gland as a reference (index score of 2), the chief cells and oxyphilic cell tissues of the diseased parathyroid had the same intensity score of 2 as that of the normal parathyroid gland, and the clear water parathyroid cell had a weaker intensity score (1–1.5). Their glandular architecture, including the trabecular, follicular, or solid arrangements, did not affect the level of intensity. The thymus, thyroid, fat, fibrosis, and necrosis had very low intensities (scores of 0). The red blood cell-hemorrhage appeared dark black (intensity score -1). The thickness of the fibrotic capsule varied in the diseased parathyroid glands; however, only a very thin capsule was observed in the normal parathyroid glands. Conclusions Various degrees of fibrotic capsules in the diseased parathyroid gland may be the main factor contributing to the lower intensity during autofluorescence, and different cell types, necrosis, fibrosis, and hemorrhage may explain the appearance of heterogeneous intensity in the diseased parathyroid glands.